Notions of Context-Driven Meta-Modeling (CDMM) - Zabawa, Piotr (Czasopismo techniczne : organ Towarzystwa Politechnicznego, 2017)
The paper focuses on the meta-model notions and introduces new terminology to the meta-modeling discipline. This terminology refers to the new concept of Context-Driven Meta-Modeling (CDMM), which is more general then other approaches to defining modeling languages. In the result it extends the metamodeling domain vocabulary. All notions in the paper were introduced on the basis of the decomposition of responsibilities identified in meta-models. Till now modeling languages were assumed to be compact and monolithic structures, in contrast to good design practices, not being a subject of any decomposition. The system of notions introduced in the paper is general enough to be sufficient when Context-Driven MetaModeling Paradigm (CDMM-P) is combined with the traditional class-object paradigm.